Aktivitas Trypsin Inhibitor Berbagai Varietas Biji Kedelai (Glycine max L.) dan Perubahannya Selama Perkecambahan Biji dari Varietas Terbaik - Kanetro, Bayu; Noor, Zuheid; Indrati, Retno (Universitas Atma Jaya Yogyakarta, 2007)
This study investigated the activity of trypsin inhibitor (TI) of some soybean (Glycine max L.) varieties and the change in TI activity during seed germination of the best variety. The research was aimed to determine the best variety of soybean and germination time based on the highest TI activity. There were 5 varieties of soybeans, Paderman, Argomulyo, Kaba, Sinabung, and Ijen. The best variety of soybean was Sinabung as shown by the highest TI activity. The soybean of Sinabung variety was germinated for 6 various germination times at 12, 24, 36, 48, 60 and 72 hr. The result showed that the variation of germination time changed TI activity. TI activity decreased significantly after 36 hr of germination of soybeans. The best time of germination was 36 hr.